Minocycline, but not doxycycline attenuates NMDA-induced [Ca2+]i and excitotoxicity. Issue 1 (6th January 2021) - Lu, Yaqin; Yang, Yusheng; Chen, Wanqiang; Du, Nicole; Du, Yansheng; Gu, Huiying; Liu, Qi
Abstract : Minocycline and doxycycline, two semisynthetic second-generation tetracyclines, are reported to provide neuroprotection against brain injury and glutamate-induced neurotoxicity in neuronal cultures. Doxycycline has been postulated as the potential ideal candidate for further therapeutic development as it has fewer adverse effects than minocycline. In this study, we determined whether minocycline and doxycycline could similarly protect neurons against excitotoxic insults. We treated cultured rat cortical neurons and cerebellar granule neurons (CGN) with excitotoxic concentrations of NMDA or glutamate in the presence or absence of minocycline or doxycycline. Intracellular Ca 2+ concentration ([Ca 2+ ]i) was also measured using a Fluorescent Light Imaging Plate Reader (FLIPR; Molecular Devices) with the calcium sensitive dye Fluo-3 AM. We found that minocycline and tetracycline markedly protected neurons against NMDA- and glutamate-induced neuronal death. In contrast, the structurally related tetracycline, doxycycline, was ineffective at concentrations up to 100 μM. Furthermore, minocycline, but not doxycycline, also significantly attenuated NMDA- or glutamate-induced [Ca 2+ ]i in both cortical neurons and CGN. Our results suggest that minocycline but not doxycycline is able to directly block NMDA- or glutamate-induced excitotoxicity in neurons most likely by inhibiting NMDA- and glutamate-induced [Ca 2+ ]i. This finding may contribute to our understanding of the molecular mechanisms underlying doxycycline- and minocycline-induced neuroprotection.